2022-RA-890-ESGO Gestational trophoblastic disease in Portugal: retrospective analysis of the last 10 years in two institutions. (20th October 2022) - Ferreira, André; Costa, Luísa Leal da; Baleiras, Mafalda; Vasques, Carolina; Duarte, Tânia; Silva, Diana Neto; Baptista, Carlota; Bizarro, Rita; Simões, Pedro; Godinho, João; Casa-Nova, Mafalda; Malheiro, Mariana; et al.
Abstract : Introduction/Background: Gestational trophoblastic disease (GTD) was first described by Hippocrates around 400 BCE as 'dropsy of the uterus'. It is a rare disease that comprises a heterogeneous group of placental lesions arising from abnormal proliferation of the trophoblast. This study aims to evaluate demographic and clinical characteristics and survival outcomes of women diagnosed with GTD. Methodology: This is a cross-sectional retrospective study of patients diagnosed with GTD between January 2011 and December 2021 in two Portuguese institutions. Clinicopathological data, β-hCG levels, treatments and survival data were extracted from medical records. Results: A total of 59 women were diagnosed with GTD, with a median age of 33 years old (range 13–49). Forty patients had a previous pregnancy before diagnosis. 54 patients underwent uterine evacuation and 5 underwent hysterectomy. After histopathological examination, 48 cases were complete molar pregnancy, 9 were partial moles, 1 placental site trophoblastic tumour and 1 choriocarcinoma. 58 patients had FIGO stage I disease and 1 had FIGO stage III. We found 50 patients with a low-risk (FIGO prognostic score ≤4), 7 in the intermediate group (score of 5 or 6) and 2 with high-risk (score ≥7). 17 patients underwent adjuvant weekly intramuscular methotrexate (MTX) with a median of 12 cycles. 7 patients were treated with actinomycin D as second-line therapy due to MTX resistance. The 2 patients with FIGO prognostic score of high-risk underwent first-line chemotherapy with EMA-CO. Both 5-years progression free survival and 5-years overall survival were 97%, with only one death; the choriocarcinoma patient had a fatal pulmonary tumor embolism before starting chemotherapy. Conclusion: GTD is a rare disease, usually curable with chemotherapy, but high-risk disease can be very aggressive with worse prognosis. Despite being a rare disease, physicians' awareness is critical. Early diagnosis, correct risk stratification and prompt treatment are the main goals for cure.